2005
DOI: 10.1108/14678040510636720
|View full text |Cite
|
Sign up to set email alerts
|

Making decisions using the balanced scorecard and the simple multi‐attribute rating technique

Abstract: Purpose -The purpose of this article is to address the measure selection problem and to propose the use of a multi-criteria approach to address the problem more effectively. The main objective of this research is to propose a methodology (not a new performance measurement framework) that will support existing measurement framework(s) during the process of performance measurement systems' design, implementation and use, and to advance the decision-making process. Design/methodology/approach -Conforming to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…The SMART model, however, is independent of the alternatives. Since the ratings of alternatives are not relative, changing the number of alternatives considered will not in itself change the decision scores of the original alternatives, which is particularly useful when new alternatives or features are added to the existing comparison [9].…”
Section: Project Prioritisationmentioning
confidence: 99%
“…The SMART model, however, is independent of the alternatives. Since the ratings of alternatives are not relative, changing the number of alternatives considered will not in itself change the decision scores of the original alternatives, which is particularly useful when new alternatives or features are added to the existing comparison [9].…”
Section: Project Prioritisationmentioning
confidence: 99%
“…Other multi-criteria analysis methods have also been applied in the design and evaluation of BSCs. For example, the Simple Multi-Attribute Rating Technique (SMART) can be used to select appropriate measures for the development of a BSC system in a financial institution (Valiris et al, 2005).…”
Section: Proposed Methodology Literature Reviewmentioning
confidence: 99%
“…Registration S.T. The ED managers were asked to rank the alternatives with respect to each criterion in order, from the most to least preferred, on an easy-to-use value scale (Valiris et al, 2005).…”
Section: Key Performance Indicators Selectionmentioning
confidence: 99%
“…After the readjustment of the clinic capacity (Column D), it was revealed that the real problem facing the clinics was the over utilisation of existing resources and that the so-called unused capacity presented in previous reports was a result of faulty measurement (c.f. Valiris et al, 2005;Bayou, 2001) From the literature on capacity planning/management and performance drivers in healthcare the authors recognised two core challenges:…”
Section: Take In Table IImentioning
confidence: 99%
“…From an operations perspective Valiris et al (2005) distinguished four main reasons for problematic capacity measurement: i) the product or service mix; ii) the time period -sustainable output does not necessarily equal the outcome of the process during a short period of time; iii) the product or service specification, and iv) capacity leakages. The complexity of most operations is certainly a decisive factor.…”
Section: Introductionmentioning
confidence: 99%